The Influence of Customer Perceived Value, Customer Commitment, and Halal Awareness on Repurchase Intention - Alia Cahyani; Rima Hafidz Ramadhani; Ahmad Nuh; Rizaludin Rizaludin (CV. Ulil Albab Corp, 2025)
This study investigates the influence of customer perceived value, customer commitment, and halal awareness on repurchase intention for Bingke Cakes, a specialty of West Kalimantan. The research involved 150 respondents who were consumers of Bingke Cakes. Data was collected through an online survey using a questionnaire designed to measure the variables of interest. The study found that customer perceived value, customer commitment, and halal awareness significantly influence repurchase intention for Bingke Cakes. These findings suggest that Bingke Cakes producers should focus on enhancing customer perceived value, fostering customer commitment, and emphasizing halal awareness to increase repurchase intention among consumers.